SOCIAL EDUCATION THROUGH DIGITAL LITERACY AMONG INDONESIAN FEMALE MUSLIM ACTIVISTS: The Experience of Abdurrahman Wahid’s Daughters (JOURNAL OF INDONESIAN ISLAM, 2020)
This article analyses the experience of Indonesian women Muslim activists in conducting social education through digital literacy. It focuses on Twitter as the media of digital literacy they actively employ. Responses to tweets are assessed with Anderson’s taxonomic indicators (namely remembering, understanding, applying, analyzing, evaluating, and creating) in order to know the cognitive level of society under the framework of social education. With regards to the notion of the Indonesian women Muslim activists, this article refers to four daughters of the late Abdurrahman Wahid, Alissa Qotrunnada, Zannuba Ariffah Chafsoh, Anita Hayatunnufus, and Inayah Wulandari, being known as social activists on religions, multiculturalism, equality, democracy, and human rights, particularly through their tweets. This paper argues that women Muslim activists play a key role in making use of digital media for leading the Indonesian Muslim community to become a critical society. Through the enhancement of the society’s cognitive level, it further argues, those women Muslim activists have skillfully developed digital literacy-based social education for people’s socio-political criticism.